Analysis of a Combination Therapy Protocol for the Treatment of Oral Mucous Membrane Pemphigoid: A Retrospective Case Series Study - Simona Santonocito; Alessandro Polizzi; Marco Matarese; Rosario Caltabiano; Gaetano Isola (International Journal of Dentistry)
Mucous membrane pemphigoid (MMP) is an autoimmune-based bullous disease affecting the mucous membranes, mainly oral and ocular. One of the most common clinical manifestations is desquamative gingivitis (DG), characterized by intense symptoms and functional limitations. The dentist is among the first specialists to observe DG and, therefore, must be able to diagnose it. In this regard, the purpose of the present study was to evaluate the efficacy and safety of a clinical protocol for the topical management of patients with DG and MMP buccal lesions. Thirteen patients with clinical and histologic diagnoses of MMP-localized DG in the oral cavity were retrospectively enrolled. Each patient received topical treatment with clobetasol propionate oral gel 0.05%; nicotinamide; oral probiotic (contains Bifidobacterium lactis HN019, Kluyveromyces marxianus fragilis B0399, colostrum, and biotin); and doxycycline. Before and after 3 months of therapy, clinic records were collected for each patient. Seven patients (53.8%) had a complete response to treatment; four patients (30.8%) had a partial response to treatment; and, finally, two patients (15.4%) had no benefit from therapy. Dental management of patients presenting solely with oral manifestations of MMP may involve the use of topical corticosteroids, doxycycline, vitamin supplements, and probiotics and associating professional oral hygiene procedures.